Low molecular weight xanthan gum for treating osteoarthritis. (15th May 2017) - Han, Guanying; Chen, Qixin; Liu, Fei; Cui, Zan; Shao, Huarong; Liu, Fuyan; Ma, Aibin; Liao, Joshua; Guo, Bin; Guo, Yuewei; Wang, Fengshan; Ling, Peixue; et al.
Graphical abstract: Highlights: An low molecular weight of xanthan gum (1 × 10 6 to 1.5 × 10 6  Da) injection preparation maybe become an excellent candidate long-acting drug for treating osteoarthritis. The effectiveness treatment of low molecular weight of xanthan gum in osteoarthritis outperforms an existing clinical medication-sodium hyaluronate. The potential mechanism of low molecular weight of xanthan gum for the anti-osteoarthritis effect is attributed to regulate the protein levels of caspase-3, bax, and bcl-2. Abstract: Osteoarthritis (OA) is one of the most common chronic diseases and characterized by degradation of articular cartilage. We have previously reported xanthan gum (XG) injection preparation with high molecular weights ( Mw ) in ranging from 3 × 10 6  Da to 5 × 10 6  Da (HM-XG) could enhance the viscosity of synovial fluid, protect joint cartilage in rabbit, and the therapeutical effect has no significance difference with an existing clinical medication (sodium hyaluronate, SH) at the same injection frequency (once weekly for 5 weeks). Herein, we prepared a XG injection preparation with a low M w (LM-XG) in ranging from 1 × 10 6  Da to 1.5 × 10 6  Da, and evaluated the therapeutical effect for OA therapy at once every 2 weeks for 5 weeks with an SH at once weekly for 5 weeks as reference. The model of OA was induced using anterior cruciate ligament transection (ACLT) in a rabbit in vivo and also using sodium nitroprusside (SNP) in cell culture in vitro . The results showed that LW-XG could also protect cartilage from damage, decrease the concentration of nitric oxide (NO) in synovial fluid and reverse the amplification of the knee joint width similar to HM-XG as our previously reported. At the cellular level, LW-XG promotes proliferation while decreases apoptosis of chondrocytes. Mechanistically at the molecular level, these effects are elicited via down-regulation of the protein levels of caspase-3 and bax and up-regulation of the protein levels of bcl-2 in cartilage in both in vivo and in vitro. These results showed that LW-XG maybe become an excellent candidate long-acting drug for treating OA.